2018
DOI: 10.1001/jamacardio.2018.0125
|View full text |Cite
|
Sign up to set email alerts
|

Association of Albuminuria With Major Adverse Outcomes in Adults With Congenital Heart Disease

Abstract: Albuminuria is common and is associated with increased risk for adverse outcome in patients with ACHD with biventricular circulation. Albuminuria appears especially useful in stratifying risk in patients categorized as NYHA functional class 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Proteinuria has emerged as an important vascular risk factor for adverse cardiovascular events across a range of populations. [1][2][3] It has been suggested that proteinuria not only reflects glomerular damage, but also is a sensitive indicator of generalized endothelial dysfunction and capillary vasculopathy that allows penetration of atherosclerotic lipoproteins into vessel walls. 4 There appears to be a particularly strong association between proteinuria and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Proteinuria has emerged as an important vascular risk factor for adverse cardiovascular events across a range of populations. [1][2][3] It has been suggested that proteinuria not only reflects glomerular damage, but also is a sensitive indicator of generalized endothelial dysfunction and capillary vasculopathy that allows penetration of atherosclerotic lipoproteins into vessel walls. 4 There appears to be a particularly strong association between proteinuria and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A study including 1102 adult patients with CHD (mean age 36.0 ± 14.2 years, 9% had eGFR <60 mL/min/1.73 m 2 ) yielded an 8.3 mL/min/1.73 m 2 (7.3–9.4 mL/min/1.73 m 2 ) decrease in eGFR per 10-year increase in age [ 2 ]. Kidney dysfunction in adults with CHD has drawn the attention of physicians because it is associated with increased long-term mortality [ 2 , 3 , 10 ]. However, in our study, CR-CKD was detected in 2-year-old patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Diuretic usage is associated with a decreased eGFR and increased incidence of albuminuria in patients with CHD [ 2 , 3 , 17 ]. Although it is used for controlling congestive heart failure in patients with CHD, loop diuretic usage in patients with non-CR-CKD was higher than in those with CR-CKD in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations